A microenvironment-modulating dressing with proliferative degradants for the healing of diabetic wounds - Lianghui Cheng; Zhiyong Zhuang; Mingming Yin; Yuan Lu; Sujuan Liu; Minle Zhan; Liyuan Zhao; Zhenyan He; Fanling Meng; Sidan Tian; Liang Luo (Nature Communications)
Abstract Diabetic wounds are usually entangled in a disorganized and self-perpetuating microenvironment and accompanied by a prolonged delay in tissue repair. Sustained and coordinated microenvironment regulation and tissue regeneration are key to the healing process of diabetic wounds, yet they continue to pose a formidable challenge. Here we report a rational double-layered dressing design based on chitosan and a degradable conjugated polymer polydiacetylene, poly(deca-4,6-diynedioic acid) (PDDA), that can meet this intricate requirement. With an alternating ene-yne backbone, PDDA degrades when reacting with various types of reactive oxygen species (ROS), and more importantly, generates proliferative succinic acid as a major degradant. Inheriting from PDDA, the developed PDDA-chitosan double layer dressing (PCD) can eliminate ROS in the microenvironment of diabetic wounds, alleviate inflammation, and downregulate gene expression of innate immune receptors. PCD degradation also triggers simultaneous release of succinic acid in a sustainable manner, enabling long-term promotion on tissue regeneration. We have validated the biocompatibility and excellent performance of PCD in expediting the wound healing on both diabetic mouse and porcine models, which underscores the significant translational potential of this microenvironment-modulating, growth-promoting wound dressing in diabetic wounds care.